Methods for in vitro CRISPR/CasRx-Mediated RNA Editing - Chuang, Yu-Fan; Wang, Peng-Yuan; Kumar, Satheesh; Lama, Suraj; Lin, Fan-Li; Liu, Guei-Sheung (Frontiers in Cell and Developmental Biology, 2021)
Specific changes in the genome have been accomplished by the revolutionary gene-editing tool known as clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas) system. The advent of programmable RNA-editing CRISPR/Cas nucleases has made this gene-editing tool safer and more precise. Specifically, CasRx, a family member of Cas13d family, has shown great therapeutic potential. Here we describe the in vitro methods of utilizing this powerful RNA-editing platform and determine the RNA-editing efficiencies for CasRx with different forms of guide RNAs (also known as gRNA or sgRNA).